The Spatial Planning Policy Implementation of Gianyar Regency in Preserving Paddy Field - Vavorita, Barlianti (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
The global phenomenon of agricultural land conversion struck in the most famous island in Indonesia, Bali especially Gianyar Regency. In 2017, Gianyar Regency known as one of Bali rice barns and got the highest Food Security Index (IKP) scores in Indonesia. Therefore, in order to maintain the availability of agricultural land to support the food security, the intervention from government needed. In this case is the spatial planning policy. This study explores the implementation of spatial planning policy in Gianyar Regency, Bali. The research use qualitative approach focused on four factors of effective implementation proposed by Edward III: communication, resource, disposition and bureaucratic structure. This study use interview, observation and documentary study to collect the data. The result shows that the communication among the local authority is need to improve because of inconsistently transmission to the farmer/ public. Furthermore, the bureaucratic structure fragmented in a local level result in less effective implementation. While for another factors is not urgently enough for further consideration.